“Ele não seria como seu pai”: raça, gênero, classe e sexualidade na ficção autobiográfica de James Baldwin - Luiza de Almeida Carminati (2024)
This research is motivated by the desire to contribute to the field of Literary Studies that focuses on texts historically excluded from the canon, that is, narratives that seek to give voice to subjects other than those of the Western literary tradition, characterized by being mostly white, patriarchal and Eurocentric. Thus, we worked with Go Tell It on the Mountain, by American writer James Baldwin. The author's first novel, the book was first published in 1953. The narrative, composed by strong autobiographical elements, follows John Grimes, a black boy from Harlem, his family and his community. The primary aim of the research is to consider how the novel can be interpreted in the light of contemporary biographical criticism. Through critical analysis, we discuss how he operates the insertion of the biographical into fiction, considering the imaginative/inventive specificities of writing. Therefore, we seek to understand how the author mobilizes issues of race, gender, class and sexuality in his writing, as well as relating his approach to the Brazilian reality, through a reflection on the idea of Escrevivência. In this way, we can see how the collective dimension of his writing - the characteristic of extrapolating the domain of the individual and being concerned with issues that involve a broader historical reverberation - contributed to the creation of an Afrocentric poetics.